Heat Shock Proteins Revisited: Using a Mutasynthetically Generated Reblastatin Library to Compare the Inhibition of Human and Leishmania Hsp90s. (19th February 2018) - Mohammadi‐Ostad‐Kalayeh, Sona; Stahl, Frank; Scheper, Thomas; Kock, Klaus; Herrmann, Christian; Heleno Batista, Fernanda Aparecida; Borges, Júlio César; Sasse, Florenz; Eichner, Simone; Ongouta, Jekaterina; Zeilinger, Carsten; Kirschning, Andreas
Abstract: Thirteen new reblastatin derivatives, with alkynyl, amino and fluoro substituents on the aromatic ring, were prepared by a chemo‐biosynthetic approach using an AHBA(−) mutant strain of Streptomyces hygroscopicus, the geldanamycin producer. The inhibitory potencies of these mutaproducts and of an extended library of natural products and derivatives were probed with purified heat shock proteins (Hsps), obtained from Leishmania braziliensis (LbHsp90) as well as from human sources (HsHsp90). We determined the activities of potential inhibitors by means of a displacement assay in which fluorescence‐labelled ATP competes for the ATP binding sites of Hsps in the presence of the inhibitor in question. The results were compared with those of cell‐based assays and, in selected cases, of isothermal titration calorimetry (ITC) measurements. In essence, reblastatin derivatives are also able to bind effectively to the ATP‐binding site of LbHsp90, and for selected derivatives, moderate differences in binding to LbHsp90 and HsHsp90 were encountered. This work demonstrates that parasitic heat shock proteins can be developed as potential pharmaceutical targets. Abstract : Heat shock protein (Hsp) inhibition in parasites : New reblastatin derivatives, prepared by mutasynthesis complemented with a library of other Hsp inhibitors, were evaluated in cell‐based and in in vitro ATP displacement assays, the latter utilising purified human HsHsp90 and LbHsp90 from L. braziliensis . The study paves the way for finding selective inhibitors of parasitic heat shock proteins.